PENGARUH PENERAPAN PENILAIAN DIRI (SELF ASSESSMENT) DALAM MEMBENTUK KEBIASAAN BERPIKIR PRODUKTIF (HABIT’S OF MIND) SISWA - Ratih Permana Sari; Sri Setiawaty (Jurnal Dedikasi Pendidikan, 2017)
Balancing the mental and individual skills of individuals to learn about everything they want or need to do with their lives is one thing that matters for the real purpose of education. One effort that can be done is to train and develop students' productive thinking habits through an application of formative assessment that can monitor the development of students. This study aims to determine the effect of the application of self-assessment in the form of productive thinking habits of students applied to the subject matter of the colloidal system. The research method using quasi experiment with "Nonequivalent Control Group Pretest-posttest Design" design involves 2 classes that come from class XI IPA 6 as experimental class and XI IPA 11 as control class. The data used is descriptive quantitative. The results showed that the application of self-assessment on classroom and laboratory learning for the experimental and control class has shown a good percentage achievement in each indicator habits of mind trained although some indicators need to be improved. For each indicator of productive thinking habits (self regulation, critical thinking and creative thinking) the experimental and control classes experienced better improvement after the application of self-assessment. The result of correlation between self-assessment toward productive thinking habits for experiment class and control class shows that there is significant relation indicated by rhitung> r table that is 0,362> 0,301.